Evaluation of a bi-epitope of glyceraldehyde 3-phosphate dehydrogenase and Disorganized Muscle in the protection of sheep against Haemonchus contortus - Díaz, Arnielis (2018)
The aim of this study was to evaluate the protection capacity in sheep against Haemonchus contortus using a peptide that mimics epitopes of glyceraldehyde 3- phosphate dehydrogenase (GAPDH) and the Disorganized Muscle (DIM-1) of H. contortus. A genotypic phage library (7 aa-GGG) was evaluated with the use of a polyclonal anti-H. contortus antibody IgG. After three rounds of selection, 120 clones were sequenced and the amino acid sequences were aligned. Peptide sequences similar to DIM-1 and GAPDH were selected, and a peptide with these two epitopes was synthesized. A group of four rams with the bi-epitope and another similar group with the adjuvant were immunized on days 0, 7, 14 and 28. One week after the last vaccination all the animals were challenged with 1250 L3 larvae of H. contortus. The average number of eggs per gram of feces (hpg) and the parasitic load in the abomasum of the group vaccinated 70 days after the infestation were reduced by 57.9 and 52.7%, respectively. Serum IgG levels were significantly higher in the vaccinated group; it also increased the number of eosinophils and increased the hemoglobin.